Parents’ Perception Towards Online Education - Jony, Md. Solaiman; Sultana, Sazia (International Journal of Educational Innovation and Research, 2023)
Due to COVID-19 pandemic educational institutions of Bangladesh was forced to shut down and had no option but to operate online education for the continuation of education by maintaining social distancing. As an important stakeholder of children’s education, parents played an influential role for supporting students’ online education during the crisis moment. However, despite numerous benefits of online education for the continuation of learning it is comparatively newer concept for many of the parents in Bangladesh. This study was an attempt to explore parents’ perception of online education through different factors. A total of 350 parents were asked regarding the online education and its usefulness in the context of global crisis by using a survey. A descriptive statistic is used to analyze the responses of the parents and the results indicated that parents were overall satisfied with the introduction and application of online education during the pandemic. However, parents claimed lack of digital devices and ability to use technology, poor or unstable internet connection, physical absence of teacher/instructor, lack of assessment and poor self-regulation are the barriers of online education. Moreover, parents considered that traditional learning is preferable to online learning.